Two new species of the genus Sinotilla Lelej, 1995 (Hymenoptera: Mutillidae), with notes on taxonomic characters - Okayasu, Juriya (Zootaxa, 2017)
Sinotilla calopoda sp. nov. (Indonesia, Jawa Barat) and S. ohbayashii sp. nov. (China, Fujian) are described and illustrated based on females. A key to species (females) of the genus Sinotilla is given. The importance of head shape for taxonomy is discussed.